2018
DOI: 10.3892/etm.2018.5827
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑let‑7e regulates the progression and development of allergic rhinitis by targeting suppressor of cytokine signaling 4 and activating Janus kinase 1/signal transducer and activator of transcription 3 pathway

Abstract: Abstract. The present study aimed to explore the microRNA-let-7e (miR-let-7e) expression in allergic rhinitis (AR), and to investigate the underlying molecular mechanisms. miR-let-7e expression in the nasal mucosa of mice and patients with AR were detected. The expression levels of three inflammatory factors, including histamine, immunoglobulin E and tumor necrosis factor-α (TNF-α), in the blood of AR mice and in interleukin (IL)-13-stimulated nasal epithelial cells (NECs) were also measured. Furthermore, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…[ 1 ] observed that miRNA-143 was significantly downregulated in the nasal mucosal tissues of AR patients and inhibited the production of inflammatory cytokines and mucus by nasal epithelial cells. MiRNA-let-7e has been shown to regulate the progression and development of AR via its anti-inflammatory effects [ 15 ]. Together, these reports have demonstrated that miRNAs play a significant role in the regulation of AR.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] observed that miRNA-143 was significantly downregulated in the nasal mucosal tissues of AR patients and inhibited the production of inflammatory cytokines and mucus by nasal epithelial cells. MiRNA-let-7e has been shown to regulate the progression and development of AR via its anti-inflammatory effects [ 15 ]. Together, these reports have demonstrated that miRNAs play a significant role in the regulation of AR.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, let-7e downregulated TLR4 and reduced pro-inflammatory signals, such as TNF, IFN-alpha, IL-6, IL-17, MCP-1, MIP-1, and IP-10 ( 53 , 55 , 57 ). Moreover, let-7e targeted the suppressor of cytokine signaling 4 (SOCS4) and regulated IL-13 expression in an allergic process ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among these aberrant miRNAs, miR-124 and miR-16 were decreased, and miR-221 was increased, which are consistent with previous reports [17,[23][24][25], indicating the reliability of our microarray. Let-7e was chose for subsequent investigation due to its important role in regulation of inflammatory response in various diseases [26][27][28]. However, the underlying mechanisms of let-7e in the inflammatory reactions of ALI remain unclear until now.…”
Section: Let-7e Was Upregulated In Lung Tissues and Balf In Ali Micementioning
confidence: 99%